Phasic Store-Operated Ca2+ Entry During Excitation-Contraction Coupling in Skeletal Muscle Fibers From Exercised Mice - Lilliu, Elena; Hilber, Karlheinz; Launikonis, Bradley S.; Koenig, Xaver (Frontiers in Physiology, 2020)
Store-operated calcium entry (SOCE) plays a pivotal role in skeletal muscle physiology as, when impaired, the muscle is prone to early fatigue and the development of different myopathies. A chronic mode of slow SOCE activation is carried by stromal interaction molecule 1 (STIM1) and calcium-release activated channel 1 (ORAI1) proteins. A phasic mode of fast SOCE (pSOCE) occurs upon single muscle twitches in synchrony with excitation-contraction coupling, presumably activated by a local and transient depletion at the terminal cisternae of the sarcoplasmic reticulum Ca2+-stores. Both SOCE mechanisms are poorly understood. In particular, pSOCE has not been described in detail because the conditions required for its detection in mouse skeletal muscle have not been established to date. Here we report the first measurements of pSOCE in mouse extensor digitorum longus muscle fibres using electric field stimulation (EFS) in a skinned fibre preparation. We show moderate voluntary wheel running to be a prerequisite to render respective muscle fibres susceptible for EFS, and thereby define an experimental paradigm to measure pSOCE in mouse muscle. Continuous monitoring of the physical activity of housed mice revealed an optimal training period of 5-6 days, whereby best results negatively correlated with running distance and speed. A comparison of pSOCE kinetic data in mouse with those previously derived from rat muscle demonstrated very similar properties and suggests the existence and similar function of pSOCE across mammalian species. The new technique presented herein enables future experiments with genetically modified mouse models to define the molecular entities, presumably STIM1 and ORAI1, and the physiological role of pSOCE in health and under conditions of disease.